Robots for a Detailed Study of Moon - Saprykin, Oleg; Tolstel, Oleg (International Journal of Psychosocial Rehabilitation, 2019)
The problem of a detailed study of the Moon is considered - the phase of the study in which a person has either not yet begun manned flights, or makes them no more than once a year. At this phase, it is very important to conduct detailed studies of the substance in various regions of the moon, which should directly affect the pace, scale and scenarios of the exploration of the moon. The authors, relying on a list of scientific research on the moon that is relevant for the coming decades, offer the appropriate tools - automatic and semi-automatic (with elements of artificial intelligence) robots. It is shown that scientific tools and the necessary robotic systems can be unified and reduced to a relatively small list.Of particular interest is the reusable use of scientific equipment and related robotic systems. Reusable execution of robots, their maintenance on the lunar surface by robots themselves or on board a near-moon station can significantly reduce the time of exploration of the moon and go to the phase of its development - the pace of research can be increased by an order of magnitude. A key element in the proposed concept should be a reusable take-off and landing vehicle (MVPA). Its creation will ensure the reusability of the use of robots on the moon. In addition, the authors conclude that it is necessary to deploy an automatic lunar orbital station (LOS) in a low lunar orbit, the main task of which will be the maintenance of replaced equipment and the refueling of MVPA.Authors present configurations of promising robot platforms for scientific equipment for a detailed study of the moon. Features of the use of anthropomorphic robotics on the moon are considered separately. Recommendations are given on its use, implementation of elements of the artificial intelligence system. In combination with proposed MVPA concept and reusable scientific equipment, the use of anthropomorphic technology will ensure the telepresence of research scientists on the moon, regardless of the fact and speed of manned flights.